Pemberdayaan Generasi Muda Bangsa dalam Memupuk Nasionalisme Melalui Kegiatan Upacara Kemerdekaan Indonesia di Gunung Eusing Sebagai Manifestasi Daripada Identitas Bangsa - Muhammad Fikri Adzkiya; Wanto Hermawan; Netri Dea Yasmin; Lulu Falah Ramadhani; Intan Tivani; Fauzyyah Pebriana; Syam Ridhollah A; Luthfi Fathurrahman; Muhammad Irfan Faiz; Muhammad Rezza; Fhadlan Hifzilah; Arija Taufiqurrahman; Muhammad Eko Surya; Abdulah Hanafi; Nida Handayani (Jurnal Informasi Pengabdian Masyarakat, 2024)
In the context of empowering the nation's young generation, the Youth Organization of Rumpun Saka and students of the University of Muhammadiyah Jakarta in community service activities carried out the 77th Indonesian independence ceremony on Mount Eusing as a manifestation of a sense of nationalism towards the nation and state. This was the first time that Leuwibatu Village held a ceremony on Mount Eusing. The difficult terrain to reach the ceremony venue is a challenge in itself, so with the collaboration between youth organizations and students, the climb can be skipped so that the independence ceremony can be held. This is an innovation as well as a solution to be able to implement activities that are considered sacred, so the existence of collaboration between these elements is very necessary. The method of implementing the activities starts from the stages of planning and preparation, implementation, and evaluation. The purpose of this activity to empower the nation's young generation is to become a culture and a pioneer that can build the spirit of nationalism and the fighting spirit of young groups, especially the young people of Leuwibatu Village. Through the potential of its resources, it can optimize the results and objectives of village development in shaping the character education of the younger generation